Inconvenientes con la tecnología en la enseñanza de la física - Orjuela Abril, Juan Carlos (Revista Científica, 2011)
The social problem in which we live, shows us a number of short comings in the education of young people, whether at home, at school, at work or in their social environment (friends). Drug addiction, alcohol abuse, television, video games, fashion, social conditions are to which young people are exposed in their daily lives, and thus take possession of these influences in the life of young and do not carry out his thinking on things that do not help in their future lives if not on the contrary, knowledge can be lost in our civilization, and that is where teachers come to act.